2021
DOI: 10.3390/nu13041375
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Zinc Status of Pregnant Women in the China Adult Chronic Disease and Nutrition Surveillance (CACDNS) 2015

Abstract: Objective: The purpose of this study was to evaluate serum zinc status of pregnant women in the China Adult Chronic Disease and Nutrition Surveillance (CACDNS) in 2015–2016. Methods: A total of 7147 apparently healthy pregnant women were randomly selected in 302 national monitoring sites. Information on age, race, residence region, education, pregnancy, and family income per annum was collected, and the concentration of serum zinc was determined. The evaluation of serum zinc status was further performed accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In the present study, the zinc deficiency rate of the elderly in CACDNS 2015 was 8.68%, which was quite lower than the recommended 20% and was also lower than the 12.2% prevalence for 131 middle-aged and elderly people living in Wuhan reported in 2010 [ 14 ]. However, when comparing with the other population in CACDNS 2015, we found that the zinc deficiency rate in elderly were higher than the adult aged 18–60y (6.04%) [ 16 ], the childbearing women (5.03%) [ 17 ] and the pregnant women (3.5%) [ 18 ]. Therefore, it is still necessary to continue to pay more attention to this population.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the zinc deficiency rate of the elderly in CACDNS 2015 was 8.68%, which was quite lower than the recommended 20% and was also lower than the 12.2% prevalence for 131 middle-aged and elderly people living in Wuhan reported in 2010 [ 14 ]. However, when comparing with the other population in CACDNS 2015, we found that the zinc deficiency rate in elderly were higher than the adult aged 18–60y (6.04%) [ 16 ], the childbearing women (5.03%) [ 17 ] and the pregnant women (3.5%) [ 18 ]. Therefore, it is still necessary to continue to pay more attention to this population.…”
Section: Discussionmentioning
confidence: 99%
“…The on-site survey phase is an effort involving live, face-to-face interviews and anthropometric measurements, together with the administration of a questionnaire by trained interviewers. The standard questionnaire, which was designed based on the questionnaire of the China Adult Chronic Disease and Nutrition Surveillance (CACDNS) that was carried out every three years in China [ 16 ], contains information about the basic personal information (age, gender, marital status, education level, occupation type, family income, etc. ), the prevalence of behavioral risk factors (smoking, alcohol consumption, diet, physical activity), family history of hypertension, etc.…”
Section: Methodsmentioning
confidence: 99%
“…The study was conducted based on the WHO STEPwise approach to chronic disease risk factor surveillance with slight modifications and included a questionnaire survey and anthropometric measurements. A standard questionnaire was designed based on the China Adult Chronic Disease and Nutrition Surveillance questionnaire with minor adjustments 20. This instrument included questions related to the respondent’s baseline characteristics (age, sex, marital status, nationality, region and residence), SES (education, occupation and income) and health behaviours (smoking, alcohol consumption and diet).…”
Section: Methodsmentioning
confidence: 99%
“…A standard questionnaire was designed based on the China Adult Chronic Disease and Nutrition Surveillance questionnaire with minor adjustments. 20 This instrument included questions related to the respondent’s baseline characteristics (age, sex, marital status, nationality, region and residence), SES (education, occupation and income) and health behaviours (smoking, alcohol consumption and diet). Trained investigators conducted face-to-face household interviews.…”
Section: Methodsmentioning
confidence: 99%